Genetics of conditional extended mycelial cell viability of Streptomyces minutiscleroticus in deep starvation phase implicates the involvement of (p)ppGpp, clpX, and a histidine kinase sasA - Chatupale, Vaidehi; Pohnerkar, Jayashree (Frontiers in Microbiology, 2024)
Bacterial lifespan ranges from a few hours to geological timescales. The prolonged survival trait under extreme energy starvation is essential for the perpetuation of their existence. The theme for long-term survival [long-term stationary phase (LTSP)] in the non-growing state may be dependent on the diversity in the environmental niche and the lifestyle of the bacteria, exemplified by longevity studies, albeit few, with model organisms. In the present study, we characterized the LTSP of mycelial cells of Streptomyces Minutiscleroticus, which remain metabolically active, demonstrate ongoing protein synthesis—killed by protein synthesis inhibitors—and remarkably by the cell-wall synthesis inhibitors, vancomycin, and ampicillin, suggesting “growth.” Their rapid turnover is also evident in ~10-fold loss of colony-forming unit (CFU) over a year, suggesting that for the death of one “old” cell, slightly less than one “new” cell is born. This longevity is consequent to (i) induction of the gene expression program effected by non-metabolizable, non-ionic osmolyte, sucrose, thus conditional, and (ii) possibly rendering this carbon utilizable by the production of a slow hydrolytic activity generating glucose, reinforcing the relevance of low-level energy resource for long term survival in the starvation phase. The viability parameters of LTSP cells measured through up to 90 days suggest that the stationary phase transitioning into LTSP following nutrient exhaustion is nearly quantitative. Expectedly, the viability in LTSP is (p)ppGpp/RelA dependent. Whereas mutation in chaperone clpX, negatively affects survival in stationary phase, overexpression of signal sensor-transducer histidine kinase, SasA8, enhances cell survivability. The relevance of longevity functions identified here requires further deduction of the genetic program.